Association between Stretching Exercise with Virtual Reality Game and Over Head Pulley of Frozen Shoulder Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objective: Frozen Shoulder (FS) or adhesive capsulitis is the most common musculoskeletal condition that causes pain and extensive restriction of joint motion. Virtual Reality (VR) provides a new option that is expected to help the rehabilitation program. The objective of the study was to compare the effect of stretching exercises with virtual reality games (VRG) and Over Head Pulley (OHP) through shoulder joint motion range (JMR) improvement and functional ability of FS. Method: This research was conducted on July to September 2012, in Medical Rehabilitation Outpatient Unit of Dr. Soetomo General Hospital Surabaya. The samples were frozen shoulder patients. These inclusion criteria were new or old unilateral FS patients, the limitations of shoulder JMR both passive and active, with a minimum limit of 30 ° compared to normal shoulder JMR at least 2 shoulder movements, flexion and abduction between 6 weeks to 6 months, aged 35-65 years. Result: The One-Sample Kolmogorov-Smirnov Test on the age range obained no significant differences (p = 0.418), the chi-square test on the sexes showed no significant differences (p = 1,000). The median of pleasure after treatment with the Mann-Whitney Test showed a non-significant difference (p = 0.317). Conclusion: Stretching exercises compared with VGR exercises in FS patients provided the same benefits of stretching with the OHP on improvement.